The left in history : revolution and reform in twentieth-century politics - Thompson, Willie (Pluto Press, 1997)
"The political tradition loosely termed 'the left' has been brought to crisis point as the twentieth century draws to a close. This cohesive and wide-ranging study charts the history of the left, from its origins in the French Revolution to the present crisis." "Willie Thompson focuses on the principal currents, including the rise and fall of Bolshevism, Leninism and Stalinism; the embrace and subsequent abandonment of Marxist rhetoric by former Soviet allies in the Third World; European social democracy; and 'actually existing socialism' in states such as China and Cuba. The impact of 'alternatives' to the mainstream - Trotskyism, Maoism and Eurocommunism - is assessed, and the potential for the New Left and postwar social forces such as feminism, environmentalism and 'identity' politics to facilitate renewal is evaluated. Thompson concludes that if the left is to play any part in addressing the unfinished agenda of the post-1900s, then it must develop a clear understanding of the historical lessons that follow from its earlier embodiments." "Willie Thompson is Senior Lecturer in History at Glasgow Caledonian University."--Jacket